Competitive sharing: Sri Lankan Hindus and Up-country Tamil religiosity at the Sri Pada Temple - De Silva, Premakumara (My University, 2018)
The cultural hegemony of post-colonial public religion has been one of the greatest banes to linguistic and religious minorities. Minority cultures have become invisible in a national culture increasingly dominated by a highly politicised and organised Sinhala- Buddhist polity. The politicisation of Buddhist culture is a significant aspect of the consolidation of the bi-polar ethno-racial-religious imagination in colonial and postcolonial Ceylon (Rajasingham-Senanayake 1999: 134). Though Sinhala Buddhist and Tamil Hindu linguistic communities have historically co-existed and shared a breadth of cultural and religious practices, they have emerged in the postcolonial period as opposed national communities. Nevertheless, Hinduism enjoys a certain effective uniformity of status with Buddhism, arguably due to their intertwined historical roots and ability to accommodate other deities. While Buddhism in theory is atheistic and Hinduism polytheistic, both religions are in practice polytheistic, entertain a multiplicity of gods and do not have injunctions against ‘other’ deities that religions such as Roman Catholic Christianity and Islam entail. The famous multi-religious sacred sites of Katharagama in the south, Sri Pada in central hill, Munneswarm in the North-west and Mannar in the west of the island are testimony to the co- existence of these two religions in Sri Lanka, in addition to the accommodation of Islam and Christianity.
Keywords: Competitive sharing: Sri Lankan Hindus and Up-country Tamil religiosity at the Sri Pada Temple